Determination of low level 210Pb activity in tobacco by using 61 keV beta-energy line - Dogru, M; Kumral, HM; Kulahci, F; Canbazoglu, C; Baykara, O (Kluwer Academic Publ, 2001)
The aim of this work is to study the low level Pb-210 activity as an indicator of Po-210 by using the Pb-210 61 keV beta-energy line. The 61 keV beta-energy was selected by setting the threshold and window of the double channel analyser in coincidence. This selection is convenient with the high sensitive beta scintillator (BP4) using the standard nuclear spectroscopic method.